Scientific attitudes of young children through literature-based and project-based learning organization - Veena Prachagool; Chanlada Arsaiboon (University of Muhammadiyah Malang, 2021)
Young children’s scientific attitude is basic norms of human kind to cultivated actual learning, which has been an expected to be a curious, motivated, generous and responsible person. The study aimed to investigate scientific attitude of young children through literature-based and project-based learning organization (LPBL). The participants employed were young children, aged five to six years from Mahasarakham University Demonstration School (Elementary), Thailand. The duration of the study was nine weeks. The experiment was conducted in eight weeks, four days a week and 90 minutes per day which were done in 32 times. The research instruments were 32 LPBL learning plans, learning behavior observation forms, scientific attitude inventory, and debriefing focuses group interviews. The descriptive statistics used in the study were average and standard deviation. The results showed that the young children have scientific attitudes at high level by means of LPBL learning organization. The qualitative data supported that they express scientific attitudes in accordance with nature of learning.